Dinamika Penyelesaian Permasalahan Wali Adhal: Studi Kasus Peran Kepala Kantor Urusan Agama di Kabupaten Sukoharjo - Wahyono, Tri; Wibowo, Muhammad Kurniawan Budi; Baehaqi, Baehaqi (Tasyri' : Journal of Islamic Law, 2023)
Marriages with adhal guardians still often occur in society, even though for prospective brides marriage guardians are a requirement for a valid marriage. However, in reality, in society there are still frequent marriage guardians who refuse or are reluctant to marry off their daughters for various reasons that are not acceptable according to Islamic law and the applicable laws and regulations. This research is a qualitative descriptive study aimed at getting an overview of the problems regarding marriage to an adhal guardian and the role of the KUA in resolving marriages with an adhal guardian in the Sukoharjo Regency area. Data collection techniques in this study used direct surveys, interviews and documentation studies. The data analysis technique used in this study uses interactive descriptive analysis. The results of this study drew the conclusion that the problem of the adhal guardian occurred at the KUA in the Sukoharjo Regency where from the incident of the adhal guardian's marriage where the bride-to-be who did not get the blessing or marriage guardian refused to become a marriage guardian for various reasons that were not legally acceptable,   the steps taken taken by the prospective bride and groom is by submitting a guardian judge to the Sukoharjo District Religious Court, so that the local KUA has the right to carry out the marriage and become the guardian judge for the prospective bride and groom in each sub-district. The role of the Head of KUA in the Sukoharjo Regency area in solving the problem of wali adhal basically is that the Office of Religious Affairs (KUA) only has the authority to carry out tasks according to what is stated in the Regulation of the Minister of Religion (PMA), where the Office of Religious Affairs (KUA) only plays a role in bridging the community in solving a problem including in overcoming the problem of marriage with the guardian adhal